2007
DOI: 10.1038/bdj.2006.123
|View full text |Cite|
|
Sign up to set email alerts
|

TMD and occlusion part II. Damned if we don't? Functional occlusal problems: TMD epidemiology in a wider context

Abstract: Objectives To review studies investigating how functional occlusion may relate to TMD and how bruxism may relate to TMD; to review the epidemiology of TMD and relate this to the context of clinical occlusal studies and other aetiological factors. Defi ciencies in study design are highlighted and suggestions made to improve future study designs in order to provide an evidence-base for clinical practice. Design Review article. Methods Electronic databases (MEDLINE and the Cochrane Database of Systematic Reviews)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
1
9

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 26 publications
(23 reference statements)
3
40
1
9
Order By: Relevance
“…Because of the different methods used to assess TMD symptoms, which are often subjective, literature reports that the world-wide prevalence of TMD varies between 7% and 84% of the population within an age range of 3-74 years (Luther, 2007). Mostly it seems to afflict 10% of the population over 18 years of age, where chronic pain is experienced in the Temporomandibular region (LeResche, 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the different methods used to assess TMD symptoms, which are often subjective, literature reports that the world-wide prevalence of TMD varies between 7% and 84% of the population within an age range of 3-74 years (Luther, 2007). Mostly it seems to afflict 10% of the population over 18 years of age, where chronic pain is experienced in the Temporomandibular region (LeResche, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Recent review articles (Luther, 2007;Türp and Schindler, 2012) underline that the evidence supporting a relationship between occlusion and TMD is still not voluminous, such that the authors suggested that the occlusion played a minor role in the development of the signs and symptoms Temporomandibular Disorders, noted that it would be important to establish evidence that a true cause and effect relationship exists between occlusion and TMD (Tecco et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, this is not to say that any links with malocclusion are entirely spurious -it may be that more complex interpretation is required, as described below and in Part II. 4 It is also necessary to investigate facial growth, as this will infl uence the type of malocclusion seen.…”
Section: Malocclusion As a Cause Of Tmdmentioning
confidence: 99%
“…(For a critique of this study, see the 14 pages of letters subsequently printed in an issue of the same journal). 22 The problem of distinguishing causality from correlation is returned to in Part II, 4 but the possibility that TMD causes malocclusion rather than malocclusion causing TMD should at least be considered.…”
Section: Might Tmd Cause Malocclusion? Facial Growth Malocclusion Anmentioning
confidence: 99%
See 1 more Smart Citation